Nutritional intervention and impact of polyphenol on glycohemoglobin (HbA1c) in non-diabetic and type 2 diabetic subjects: Systematic review and nmeta-analysis. Issue 5 (24th March 2017) - Palma-Duran, Susana A.; Vlassopoulos, Antonis; Lean, Mike; Govan, Lindsay; Combet, Emilie
ABSTRACT: Polyphenols have been extensively studied for their antioxidant and anti-inflammatory properties. Recently, their antiglycative actions by oxidative stress modulation have been linked to the prevention of diabetes and associated complications. This article assesses the evidence for polyphenol interventions on glycohemoglobin (HbA1c) in non-diabetic, pre-diabetic, and type 2 diabetes mellitus (T2DM) subjects. A systematic review of polyphenols' clinical trials on HbA1c in humans was performed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis. Thirty-six controlled randomized trials with HbA1c values were included. Polyphenols (extracts, supplements, and foods) were supplemented (28 mg to 1.5 g) for 0.7 to 12 months. Combining all subjects ( n = 1954, mean baseline HbA1c = 7.03%, 53 mmol/mol), polyphenol supplementation significantly ( P < 0.001) lowered HbA1c% by –0.53 ± 0.12 units (–5.79 ± 0.13 mmol/mol). This reduction was significant ( P < 0.001) in T2DM subjects, specifically ( n = 1426, mean baseline HbA1c = 7.44%, 58 mmol/mol), with HbA1c% lowered by –0.21 ± 0.04 units (–2.29 ± 0.4 mmol/mol). Polyphenol supplementation had no significant effect ( P > 0.21) in the non-diabetic ( n = 258, mean baseline HbA1c = 5.47%, 36 mmol/mol) and the pre-diabetic subjects ( n = 270, mean baseline HbA1c = 6.06%, 43 mmol/mol) strata: –0.39 ± 0.27 HbA1c% units (–4.3 ± 0.3 mmol/mol), and –0.38 ± 0.31 units (–4.2 ± 0.31 mmol/mol), respectively. In conclusion, polyphenols can successfully reduce HbA1c in T2DM without any intervention at glycemia, and could contribute to the prevention of diabetes complications.